Flexible high performance hybrid AZO/Ag-nanowire/AZO sandwich structured transparent conductors for flexible Cu(In, Ga)Se2 solar cell applications. Issue 18 (22nd February 2016) - Tsai, Wen-Chi; Thomas, Stuart R.; Hsu, Cheng-Hung; Huang, Yu-Chen; Tseng, Jiun-Yi; Wu, Tsung-Ta; Chang, Chia-ho; Wang, Zhiming M.; Shieh, Jia-Min; Shen, Chang-Hong; Chueh, Yu-Lun
Abstract : We report on the fabrication of a robust and flexible transparent electrode to replace costly and fragile indium tin oxide used in flexible Cu(In, Ga)Se2 solar cells. Abstract : We report on the fabrication of a robust and flexible transparent electrode to replace costly and fragile indium tin oxide (ITO) used in flexible Cu(In, Ga)Se2 solar cells, composed of an aluminum doped zinc oxide (AZO)/Ag-nanowires/aluminum doped zinc oxide (AZO) (AAA herein) sandwich structure. The Ag-NWs networks form low-resistance, long-range pathways throughout the electrode that are able to maintain efficient charge carrier collection and extraction after strenuous mechanical bending. The improved durability of the AAA electrode enables our CIGS solar cells to maintain ∼95% of their initial power conversion efficiency, following 1000 bending cycles. In comparison, devices fabricated using AZO and ITO electrodes are only able to maintain ∼57 and ∼5%, respectively, due to crack formation and delamination of the films. This AAA sandwich structure electrode could therefore serve as a high-performance electrode for numerous flexible optoelectronic applications.